The design of 100 % renewable smart urb an energy systems: The case of Bozen-Bolzano. (15th September 2020) - Menapace, Andrea; Thellufsen, Jakob Zinck; Pernigotto, Giovanni; Roberti, Francesca; Gasparella, Andrea; Righetti, Maurizio; Baratieri, Marco; Lund, Henrik
Abstract: Sustainable urban energy planning depends on how renewable and local sources are integrated, how smart systems are implemented, and how synergies between regional and national policies are maximized. This study presents a methodology for the design of 100% renewable energy systems aiming to optimize the use of biomass and energy exchange with the national system while ensuring electricity import and export balance. The proposed procedure combines the robustness of the EnergyPLAN hourly energy system simulation model with the flexibility of multiple-criteria decision analysis. The result is a suitable methodology able to identify the best energy scenario based on a deep multi-parameter analysis from a technical point of view. A test case is proposed aiming at achieving 100% renewable energy for the Alpine city of Bozen-Bolzano in 2050. Highlights: Proposing a new methodology for sustainable urban energy systems design. Developing a suitable framework for future 100% smart and renewable-based cities. Presenting a strategy for high renewable energy penetration at the urban level. District heating allows increasing the synergies among different energy sectors. Advancing a feasible energy perspective for the Alpine city of Bozen-Bolzano 2050.